Observasi Permasalahan Pembelajaran PPKN di SMP Negeri 27 Medan - Eka Putriani Sihombing; Herlide Purba; Mario Fany Manurung; Raja Songkup Pratama; Siti Zahra Siagian; Yeni Yolanda Simbolon; Liber Siagian; Fazli Rachman (Bersatu: Jurnal Pendidikan Bhinneka Tunggal Ika, 2023)
This research focuses on observations in the junior high school (SMP) environment and the importance of this process in understanding student learning experiences and evaluating teaching. Observation in junior high school includes observationson the interaction of students, teachers and the learning environment. Through this observation, research can identify problems that occur during the learning process and find solutions by implementing interesting learning models in the teacher's teaching of students. Designing learning must begin with a preliminary study of students. There are several things that need to be understood about students, namely basic abilities and learning styles. Many students are still not interested in learning.